Two mutations commonly associated with daptomycin resistance in enterococcus faecium liaST120A and liaRW73C appear to function epistatically in liaFSR signaling (2018)
The cyclic antimicrobial lipopeptide daptomycin is now frequently used as a first-line therapy in serious infections caused by multidrug-resistant Enterococcus faecium. Resistance to daptomycin in E. faecium is mediated by activation of the LiaFSR membrane stress response pathway. Deletion of liaR, encoding the response regulator of the system, restores susceptibility to daptomycin, suggesting that the LiaFSR pathway is a potential target for the development of drugs that would induce hypersusceptibility to daptomycin and make it more difficult for enterococci to become daptomycin-resistant. In clinical isolates of E. faecium, substitutions in the membrane-bound histidine kinase LiaS (T120A) and its response regulator LiaR (W73C) are found together, suggesting a potential epistatic relationship in daptomycin resistance. Using in vitro phosphorylation studies, we show that while the phosphotransfer rate of wild-type LiaS and LiaST120A to either wild-type LiaR or LiaRW73C remains rapid and comparable, the LiaS-dependent dephosphorylation rate of phosphorylated LiaRW73C is markedly higher. When the two adaptive mutants LiaRW73C and LiaST210A are paired, however, LiaS-mediated LiaR dephosphorylation is restored back to wild-type levels. Taken together with earlier work showing that LiaRW73C leads to an increased level of oligomerization and subsequently favors an increased level of transcription of the LiaFSR regulon, the net effect of the two commonly found LiaST120A and LiaRW73C alleles would be to coordinately increase the strength and persistence of LiaFSR signaling and decrease daptomycin susceptibility. The in vitro approaches developed in this work also provide the basis for screens for identifying drug candidates that inhibit the LiaFSR pathway.